Introduction to Epigenetics - Paro, Renato (Learning Materials in Biosciences, 2021)
This open access textbook leads the reader from basic concepts of chromatin structure and function and RNA mechanisms to the understanding of epigenetics, imprinting, regeneration and reprogramming. The textbook treats epigenetic phenomena in animals, as well as plants. Written by four internationally known experts and senior lecturers in this field, it provides a valuable tool for Master- and PhD- students who need to comprehend the principles of epigenetics, or wish to gain a deeper knowledge in this field. After reading this book, the student will: Have an understanding of the basic toolbox of epigenetic regulation Know how genetic and epigenetic information layers are interconnected Be able to explain complex epigenetic phenomena by understanding the structures and principles of the underlying molecular mechanisms Understand how misregulated epigenetic mechanisms can lead to disease